Pengaruh Level Pemberian Bokashi Cair Berbahan Dasar Limbah Biogas (Slurry) dan Ekstrak (Chromolaena odorata) terhadap Pertumbuhan Awal Lamtoro (Leucaena leucocephala) - Bruno Sengkoen (JAS, 2019)
This study aims to determine the effect of liquid bokashi based on waste Biogas (Slurry) and Chromolaena odorata extract on the growth rate of lamtoro (Leucaena leuccephala). Nutrient requirements (N, P, K) available from both the soil and liquid bocation are sufficient and can cause high growth of lamtoro plants. The study used a completely randomized design (CRD) with 4 treatments and 16 replications, with a total design of 64 poly bags. The treatment given is R0 = Without liquid bokashi, R1 = Giving bokashi liquid with a dose of 50 ml / 1 liter of water, R2 = Giving bokashi liquid with a dose of 150 ml / 1 liter of water, R3 = Giving bokashi liquid with a dose of 250 ml / 1 liter of water. The variables observed were plant height, stem diameter, number of leaf stalks, fresh weight, and dry weight. It can be concluded that the level of liquid bokashi based on biogas (Slurry) and Cromolaena odorata waste of 250 ml / 1 liter of water can or can increase the highest growth including plant height: 91.03 cm / 56 days, plant stem diameter: 0.97 cm / 56 days, number of leaf stalks: 19.46 stalks / 56 days, fresh weight: 26.74 grams / 56 days and dry weight: 8.58 grams / 56 days.